Estimating the penalty in the case of multiple crimes - Aguis, Mohamed (Journal of Human Sciences, 2022)
In this research paper, we dealt with the assessment of punishment in the case of multiple crimes in Algerian legislation, where we highlighted that the punishment estimated by the criminal judge for the offender in the case of fictitious polygamy, that is, the offender. The perpetration of the verb may have several descriptions, as well as a true plural, which means the plurality of verbs and the multiplicity of descriptions associated with it. to whom the offender came.And we concluded that the legislator has devoted a rational criminal policy in this regard, in line with this approach taken by most of the world's leading legislation in the field of individualizing punishment with regard to the multiplicity of crimes, as it adopted the method of description. The most severe punishment when it comes to the case of illusory pluralism, but if it comes to real pluralism, he may adopt the method of physical summation of penalties and the system of integrating penalties.